SOCIOLINGUISTICS ANALYSIS OF LANGUAGE STYLE IN “BEAUTY AND THE BEAST” MOVIE ANALISIS SOSIOLINGUISTIK TERHADAP GAYA BAHASA DALAM FILM "BEAUTY AND THE BEAST - Nayzita Rachel Syahirah; Nurul Fadhillah; Muhammad Ilham, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The research's title is Sociolinguistics Analysis of Language Style in “Beauty and the Beast” Movie. The method employed by the researcher was descriptive qualitative. The researcher employed Martin Joo's (1976) notion of language style, The researcher discovered that the film "Beauty and the Beast" featured 78 different language styles. which is divided into: Frozen style (7), Formal style (28), Consultative style (22), Casual style (7), Intimate style (14). In this case, Formal language style is the language style that appears the most in the film Beauty and the Beast 28 times